Profile of the use and handling of antihypertensives in individuals over 60 years of age (Research, Society and Development, 2021)
Hypertension is one of the diseases that most affects the elderly, which, due to the influence of several factors, such as age and polypharmacy, may cause the incorrect administration or handling of antihypertensives. Thus, this study aims to analyze the habits of the elderly and/or their caregivers regarding the use of antihypertensives, which can be positive or negative for the treatment of the elderly. Through a virtual questionnaire in search of this information with a multivariate analysis and a cross-sectional study, 111 answers were obtained, of which 81 of the interviewees are using antihypertensives, the main ones being angiotensin receptor blocker, thiazide diuretic, angiotensin-converting enzyme inhibitor, and calcium channel blocker. It was found that most patients ingest the drugs correctly with water, and few cut the tablets and open the capsules. Regarding storage, the main places according to the survey are the kitchen and the bedroom, and many elderly people keep the medication in its original packaging. The survey presented positive results, but the errors identified could be avoided with correct and reinforced guidance from health professionals.